Comparative Analysis of Fish Culture Methods in Village Ponds of Gujarat - Ail, Sunil Kumar S.; Misra, C. K.; Chaudhari, Ajit Keshav; Landge, Asha; Dube, Kiran; Nayak, B. B.; Shenoy, Latha (Fishery Technology, 2019)
Freshwater aquaculture in Gujarat is mainly focussed on village ponds which are leased to the farmers. The state has 6860 village ponds comprising an area of 0.22 lakh ha contributing up to 9% of the inland fish production of the state. The study aimed at evaluating economic analysis of three different types of aquaculture practices viz., zerofed, bag-fed and cage cum pond integrated aquaculture production systems. Resource use efficiency indicators such as water-use index, calcium carbonate index, nitrogen-use index and energy efficiency were used to compare the aquaculture methods. The results indicated that output can be improved with system diversification. The percentage of additional net income achieved in cage cum pond integrated aquaculture production system as compared to zero-fed and bag-fed aquaculture production systems are 163.17 and 33.25% respectively. Constraints faced by farmers in upgrading their aquaculture practices were also documented. Non-availability of seed was found to be the major constraint.